Impact of offset and leg length on functional outcomes post-total hip arthroplasty: how accurate should coronal reconstruction be? - Vorimore, Camille; Innmann, Moritz Maximilian; Mavromatis, Sebastian; Speirs, Andrew; Verhaegen, Jeroen C. F.; Merle, Christian; Grammatopoulos, George (The journal of arthroplasty, 2024)
Background - Accurate hip reconstruction is associated with improved biomechanical behavior following total hip arthroplasty (THA). However, whether this is associated with improved patient-reported outcomes (PROs) is unknown. - Hypothesis/Purpose - This study aimed to: 1) describe the ability to reconstruct coronal geometry during THA without advanced technology; 2) assess whether restoration of global offset (GO) and leg length (LL) is associated with improved PROs; and 3) investigate whether increased femoral offset (FO) to compensate for reduced acetabular offset (AO) influences PROs. - Method - This was a prospective, multicenter, consecutive cohort study of 500 patients treated with primary THA without robotics or navigation. The Oxford Hip score (OHS) was obtained preoperatively and at 1-year follow-up. Supine anteroposterior pelvic radiographs were analyzed to determine AO, FO, GO, and LL relative to the native contralateral side. Contour plots for ΔOHS based on ΔLL and ΔGO were created, and ΔOHS was calculated within and outside various ranges (±2.5, ±5, or ±10 mm). - Results - In the operated hip, mean FO increased by 3 ± 6 mm (range, −16 to 27), while AO decreased by 2 ± 4 mm (range, −17 to 10). The contour graph for ±2.5 mm zones showed the best outcomes (ΔOHS >25) with GO and LL centered on 0 ± 2.5 mm (P < .01). However, only 10% achieved such reconstruction. When GO and LL differences were within ±10 mm, ΔOHS was superior when both AO and FO were within ±5 mm (mean: 24 ± 10; range, −5 to 40) compared with when FO was above 5 mm to compensate for a reduction in AO (mean: 22 ± 11; range, −10 to 46; P = .040). - Conclusions - The PROs were associated with biomechanical reconstruction, and the best clinical improvement can be expected when GO and LL differences are both within 2.5 mm. Maintenance of AO is important, as compensation by increasing FO is associated with inferior OHS.
Gesehen am 05.03.2025